JILBAB: BUDAYA POP DAN IDENTITAS MUSLIM DI INDONESIA - Lina Meilinawati (IBDA` : Jurnal Kajian Islam dan Budaya, 2016)
The purpose of this study is to examine jilbab as a pop culture and Indonesian moslem identity. The use of jilbab (a headscarf or a head covering) for moslem women has gained its popularity since the last twenty year. This phenomenon is interesting to be investigated particularly from diverse jilbab or veiling practices in many different ways. Indonesian moslem women, for instance, used styles of jilbab and fashion which are different from those worn by moslem women in other countries. Hence, this shows characteristics of Indonesian moslem women in wearing or using jilbab which becomes an identity. Many scholars see identity as a product of social construction, and a fluid concept. This is due to the emergence of various identities resulted from different contexts. For the theoretical framework, this study uses Barthes semiotic analysis to interpret and decode the signs attached to jilbab and Indonesian moslem fashion as a part of pop culture and a new identity. The result of the study indicates that jilbab as a headscarf changes from time to time in terms of its use and styles. Jilbab styles worn by Indonesian moslem women adopted both local and global styles. This demonstrates the hybrid identity of Indonesian moslem women in wearing or using jilbab.